Ta’lîm Al-‘Anāshir Al-Lughawiyyāh Min Al-Kalimāt Al-Indùnîsiyyah Dzāt Ashl ‘Arabiy Fî Mu’jam Al-Lughah Al-Indùnîsiyyah Al-Kabîr (KBBI) - Arif Taufikurrahman; Dinda Selvia (Ukazh: Journal of Arabic Studies, 2021)
كما أكبر عدد من المسلمين في العالم، واندونيسيا هي مألوفة جدا مع اللغة العربية باعتبارها لغة القرآن الكريم. واتضح حوالي 15٪ من الكلمات الاندونيسية مشتقة من اللغة العربية. فبهذا، تهدف هذه الدراسة إلى معرفة وجود الكلمات الإندونيسية ذات أصل عربي في معجم اللغة الإندونيسية الكبير (KBBI) حرف B إلى F، ومعرفة كيفية الاستيفادة من تلك الكلمات في تعليم العناصر اللغوية الثلاثة؛ الأصوات، المفردات، والقواعد (النحو والصرف). أتت الباحثة بعرض الكلمات ذات أصل عربي، وكذا أتت الباحثة بتحليل معنى للكلمات ذات أصل عربي من مفهومها في اللغة العربية واللغة الإندونيسية. إن هذه الدراسة تسلك المنهج الوصفي التحليلي التطبيقي، وذلك بمقارنة بين اللغتين (اللغة الإندونيسية واللغة العربية) حيث إن هذا البحث يعتمد على المكتبة أكثر؛ لأنه يحتاج إلى المعلومات والقراءات. أثبت الدراسة وجود الكلمات الإندونيسية ذات أصل عربي في معجم اللغة الإندونيسية الكبير (KBBI) وبلغ عدد الكلمات 143 لحرف B إلى F، وأنها يمكن الاستفادة منها في تعليم العناصر اللغوية الثلاثة؛ الأصوات، والمفردات، القواعد اللغوية (النحو والصرف) لدارسي العربية من الناطقين بغيرها من خلال التدريبات. As the largest muslim population in the world, The Indonesian are quite familiar with Arabic since it is the language of Al-Quran. And infact around 15% of Indonesian words are organaly come from Arabic.so that, this study aims to determine the existence of Indonesian words from Arabic originin in Kamus Besar Bahasa Indinesia (Indonesian Dictionary) from letter B to letter F, and to find out how to use these words in the teaching of linguistic elements i.e: sound, vocabulary, and grammar (nahwu and sharf). The Researcher described the words originating from Arabic, and analyze the meaning of those words through the point of view of both Arabic and Indonesian. The method used is qualitative method with descriptive approach and research analysis, by comparing the two languages (Indonesian and Arabic) so that this study relies more on the library research method because it requires information and reading for understanding the Arabic words. This study shows the presence of Indonesian words derived from Arabic into Indonesian dictionary (KBBI). Word count is 143 from letter B to letter F, and can be used to teach three elements of Arabic; Sound, vocabulary and grammar (nahwu and sharf) for Indonesians through practice exercises.